Диаграммы классов ООП: формализация и анализ - Буй, Д.Б.; Компан, С.В. (Труды Института прикладной математики и механики, 2013)
Дан сравнительный анализ работ, посвящённых формальным моделям объектно-ориентированного программирования (ООП). Предмет исследования модель диаграммы классов (соответствующее частично упорядоченное множество). Модель класса (спецификации класса) пара функциональных бинарных отношений, одна компонента уточняет атрибуты, вторая методы. Наследование уточняется как включение графиков функций. Над классами вводятся две операции пересечение и сочленение. Формальные результаты: структура частично упорядоченного множества классов, свойства операции наложения, в терминах которой вводится операция сочленения: идемпотентность, ассоциативность, критерий коммутативности. Модель диаграммы классов можно использовать для анализа структуры классов, что позволяет выделять подсистемы, клоны и оптимизировать по соответствующему критерию саму диаграмму. Дано порiвняльний аналiз робiт, присвячених формальним моделям об’єктно-орiєнтованого програмування (ООП). Предмет дослiдження – модель дiаграми класiв (вiдповiдна частково впорядкована множина). Модель класу (специфiкацiї класу) – пара функцiональних бiнарних вiдношень, одна компонента уточнює атрибути, друга – методи. Успадкування уточнюється як включення графiкiв функцiй. Над класами вводяться двi операцiї – перетин i зчленування. Формальнi результати: структура частково впорядкованої множини класiв, властивостi операцiї накладення, в термiнах якої вводиться операцiя зчленування: iдемпотентнiсть, асоцiативнiсть, критерiй комутативностi. Модель дiаграми класiв можна використовувати для аналiзу структури класiв, що дозволяє видiляти пiдсистеми, клони та оптимiзувати саму дiаграму згiдно з вiдповiдним критерiєм. The article deals with comparative analysis of the papers dedicated to formal models of object-oriented programming (OOP). The subject of investigation is a model of a class diagram (a corresponding partially ordered set). A class model (class specifications) is a pair of functional binary relations, one component specifies the attributes, the second one – the methods. Inheritance is defined as inclusion of function graphs. Classes are subjected to the operations of intersection and junction. The junction and the intersection of class speci?cations is important as it provides for the opportunity to construct the core of a new program with two programs which allows integrating these two programs that results in the Framework version. The formal results are as follow: the structure of partially ordered set of classes, properties overlapping operation, in terms of which the operation of junction is defined: idempotency,associativity, criterion of commutativity. Model class diagram can be used to analyze the structure of classes that allows to find subsystems, clones and optimize the chart itself according to the relevant criterion.